Effective measures to improve influenza vaccination coverage among healthcare workers during and after COVID-19 - Wanyu Jia; Xue Zhang; Ruiyang Sun; Peng Li; Daobin Wang; Chunlan Song (Human Vaccines & Immunotherapeutics)
The influenza vaccine is the most effective measure to prevent influenza. The aim of this study was to evaluate the impact of measures taken by the hospital on the influenza vaccination coverage of medical staff after implementation. We collected and compared the influenza vaccination of staff in key departments from 2018 to 2022. As the results, in 2018 and 2019, the influenza vaccination rates of staff in key departments in our hospital were generally as low as 10.3% and 11.6%, respectively. After the policy of free vaccination for staff in key departments was adopted in 2020 and other incentive measures, the overall influenza vaccination rates of key departments from 2020 to 2022 were 77.2%, 71.4%, and 81.3%, respectively, which were significantly higher than the pre-2020 vaccination rates in our hospital and healthcare workers in most regions of China. In conclusion, with the implementation of several measures to promote influenza vaccination, the rate of influenza vaccination among medical staff has significantly increased.